2012
DOI: 10.1097/bsd.0b013e31825c6f7b
|View full text |Cite
|
Sign up to set email alerts
|

The Difference of Surgical Site Infection According to the Methods of Lumbar Fusion Surgery

Abstract: The infection rate of PLIF was higher than that of PF or PLF. Considering the increased infection rate in local bone grafted group and 52% of the infection cases after interbody fusion was osteomyelitis around interbody space, contaminated local bones and interbody space were suspected as major routes of contamination. The higher infection rate in single cage group than that of double cage group was attributed to vulnerability of remained avascular disk materials to infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 18 publications
1
23
0
1
Order By: Relevance
“…Notably, the elimination of potential pathogens located in the surrounding host tissues of the TEC primarily depends on the sufficiency of the local bloodstream, not the controlled release microspheres. This case is similar to some ordinary orthopaedic surgeries 4 where the incidence of infection is very low. Antibiotics released from microspheres are quickly absorbed into the bloodstream, and the diffusion distance is confined.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Notably, the elimination of potential pathogens located in the surrounding host tissues of the TEC primarily depends on the sufficiency of the local bloodstream, not the controlled release microspheres. This case is similar to some ordinary orthopaedic surgeries 4 where the incidence of infection is very low. Antibiotics released from microspheres are quickly absorbed into the bloodstream, and the diffusion distance is confined.…”
Section: Discussionsupporting
confidence: 75%
“…During the surgical operation, the open incision is exposed to air for a long time and could result in potential infection by invasive bacteria 4. Furthermore, implanted TEC have an insufficient blood supply, making the immune responses of the host ineffective at the transplantation site as well as obstructing the local delivery of antibiotics from the peripheral blood 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…58 Bone grafting, which involves implanting devitalized bone, is associated with infection rates of up to 15%. 59 A fibrin gel mix can be created by impregnating the bone graft with vancomycin-alginate beads. Chang and colleagues 60 demonstrated that this antibiotic-impregnated bone graft was capable of bactericidal activity.…”
Section: Prophylaxismentioning
confidence: 99%